The Expansion Power of the English Banking System - Watkins, Leonard L. (Quarterly Journal of Economics, 1938)
Scope and purpose of study, 1.— I. Reserve policies of London Clearing House banks: primary expansion, 2.— Customary reserve ratios, 2.— Coefficients of expansion: commercial banking system, 8.— Individual commercial banks, 10.— II. Reserve policies of the Bank of England: systemic expansion, 16. — Deposit expansion, 17. — Currency and deposit expansion, 27.— III. Coefficients of expansion as guides for banking policy and reform, 35.